IMPLEMENTASI METODE ACTIVITY BASED COSTING DALAM MENENTUKAN UNIT COST POLIKLINIK (STUDI KASUS PADA RUMAH SAKIT NASIONAL DIPONEGORO) - Santi Widia Sari; Warsito Kawedar (Diponegoro Journal of Accounting, 2018)
This research aims to determine: (1) Calculation of Activity Based Costing System to determine polyclinic tariff at Diponegoro National Hospital (RSND) in 2017, (2) Analyze polyclinic tariff differences based on hospital counting with calculations using the 2017 Activity Based Costing System, (3) Comparison between the calculation of Activity Based Costing System and traditional calculation, (4) Proving the influence of cost determination on hospital profitability.The research method used is descriptive-analytic analysis method. Data collection methods carried out in this research were using interview methods and secondary data analysis methods. The research data was obtained from the hospital's finance department, hospital outpatient installations, hospital renovation section, hospital and hospital repair. These data include, nurse salary costs, administrative costs, electricity costs, depreciation costs, building depreciation costs, facility maintenance costs and the costs of cleaning staff salaries.Based on the results of the study indicate that: (1) The method applied by the RSND to determine the polyclinic tariff is the estimated tariff, with a tariff for each poly of Rp. 28,000. (2) The tariff of the polyclinic with Activity Based Costing method gives results that are greater than the rates set by the hospital. (3) Activity-Based Costing System compared to the unit cost method provides more accurate and clear results because each activity is charged according to the cost driver. (4) The use of tariff estimates results in distortion because resource consumption is not taken into account and affects the profitability of hospitals. The difference that occurs due to the cost of each activity. The use of tariff estimation that is taken into consideration by the hospital is the competitor tariff and social condition of the community, while in Activity-Based Costing System each activity is charged according to the cost driver so that the Activity Based Costing System is able to allocate the cost of activities to each polyclinic appropriately based on each activity consumption